The Urgency of Adaptive Performance in Supporting the Transformation of Military Educational Institutions in the Digital Age: A Case Study of Army Polytechnics - David Juninhu; Reza Fathurrahman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Digital transformation has disrupted the organization of the Indonesian Armed Forces in Indonesia. The Indonesian National Army Army needs to produce reliable personnel to respond to technological developments. The mandate for developing the competence of the personnel is, among others, handed over to the Army Polytechnic. Thus, personnel in the Army Polytechnic, both military and non-military, are also required to have adaptive performance. This article discusses the urgency of adaptive performance for the Army Polytechnic in particular and military educational institutions in general and the key factors that influence the development of adaptive performance capabilities in military educational institutions. By applying the study of literature, this article shows that with the transformation of the organization and duties of the Army Polytechnic as a military educational institution, the concept of adaptive performance plays a key role. This cannot be separated from the competence and role of human resources, which are no longer sufficient and do not follow changes in responsibilities, especially with the evolution of human resource competencies and traditional technical skills towards digital. Based on the literature review results, four key factors significantly influence adaptive performance in an organization, namely the characteristics of individuals, jobs, groups, and organizations.